Smarandache BCC-algebras - Young Bae Jun (International Journal of Mathematics and Mathematical Sciences)
The notions of Smarandache BCC-algebras and Smarandache BCC-ideals are introduced. Conditions for a (special) subset to be a Smarandache BCC-ideal are given.